Broad-based employee stock options in the US: Company performance and characteristics - James C. Sesil; Maya K. Kroumova; Douglas L. Kruse; Joseph R. Blasi (Management Revue, 2007)
This paper analyses data on 490 companies with broad-based stock option plans, matched to data from CompuStat in order to compare their characteristics and performance to that of other public companies. Major findings are that 1) companies with broadbased plans have higher levels of labor productivity, employment growth, and sales growth than otherwise-similar firms; 2) productivity and profitability levels rise as broadbased plans are adopted, and 3) average compensation levels are higher among such companies both before and after the introduction of broad-based plans, indicating that stock options appear to come on top of other compensation.
Keywords: 650; broad-based stock options; firm performance; wage effect; Aktienoption; Aktienoption; Gewinnprognose; Lohnniveau